Development and Validation of a Readiness for Organizational Change Scale - Yunseong Jo; Ah Jeong Hong (SAGE Open, 2023)
This study develops and validates a comprehensive readiness for organizational change (ROC) scale. The study was conducted based on a three-stage scale development procedure. At the first stage to generate items, a literature review and in-depth interviews with subject matter experts were carried out to conceptualize and define the conceptual model of ROC. Then, an initial item pool consisting of 127 questions was developed to measure ROC and their content validity was confirmed using Delphi survey. At the second stage to develop a scale, a pilot test consisting of 224 survey responses was carried out, and then exploratory structural equation modeling, and reliability testing were conducted. As a result, 28 items with good psychometrics were selected for the final scale. At the last stage of scale evaluation, a main test consisting of 2,410 survey responses was subjected to validity and reliability testing. The newly developed scale reflects multilevel and multidimensional characteristics to allow a holistic judgment and explanation of the ROC. This measurement scale can be used to implement organizational change and future interventions.